Hybrid Pedagogical Content Knowledge (PCK): Pendekatan Baru dalam Pengembangan Kompetensi Guru MI - Rizqiyah, Silvi (Universitas Islam Zainul Hasan Genggong, 2025)
This study aims to examine the concept and implementation of the Hybrid Pedagogical Content Knowledge (PCK) approach as a new strategy in developing the competence of Madrasah Ibtidaiyah (MI) teachers. Hybrid PCK is a development of the traditional PCK model that integrates content knowledge, pedagogics, technology, Islamic values, and sensitivity to the socio-cultural context of learners. Through a descriptive qualitative approach, data were obtained through in-depth interviews, observations, and documentation studies of MI teachers and prospective teachers. The results showed that the Hybrid PCK approach is able to improve the quality of planning and implementation of contextualised, adaptive and value-based learning. However, its implementation still faces challenges such as limited facilities and not maximising the integration of this concept in the teacher education curriculum. This research recommends the integration of Hybrid PCK in LPTK training and curriculum as a strategic step to produce MI teachers who are professional, innovative, and characterised.